Dips and floors in workplace training: Gender differences and supervisors - Fitzenberger, Bernd; Muehler, Grit (Scottish Journal of Political Economy, 2015)
This article provides a detailed decomposition analysis of the gender differences in workplace training throughout the working life with a particular focus on parental leave and supervisors using personnel records from a large German firm. Females obtain less training during the early career, and more at higher age. The timing of the training gap seems to be driven by diverging career paths associated with employment interruptions. However, we find no evidence for catching-up effects after parental leave. Furthermore, including supervisor-fixed effects cannot explain the gender differences in training. The training of both male and female employees is positively associated with the training of the supervisor.
Created from Fastlane, Scopus look-up